Ultrasensitive skin-like wearable optical sensors based on glass micro/nanofibers - Zhang Lei (Institue of Optics and Electronics, Chinese Academy of Sciences, 2020)
Electronic skin, a class of wearable electronic sensors that mimic the functionalities of human skin, has made remarkable success in applications including health monitoring, human-machine interaction and electronic-biological interfaces. While electronic skin continues to achieve higher sensitivity and faster response, its ultimate performance is fundamentally limited by the nature of low-frequency AC currents. Herein, highly sensitive skin-like wearable optical sensors are demonstrated by embedding glass micro/nanofibers (MNFs) in thin layers of polydimethylsiloxane (PDMS). Enabled by the transition from guided modes into radiation modes of the waveguiding MNFs upon external stimuli, the skin-like optical sensors show ultrahigh sensitivity (1870 kPa-1), low detection limit (7 mPa) and fast response (10 μs) for pressure sensing, significantly exceeding the performance metrics of state-of-the-art electronic skins. Electromagnetic interference (EMI)-free detection of high-frequency vibrations, wrist pulse and human voice are realized. Moreover, a five-sensor optical data glove and a 2×2-MNF tactile sensor are demonstrated. These initial results pave the way toward a new category of optical devices ranging from ultrasensitive wearable sensors to optical skins.